PCL-PU three-layer composite fiber heart valve prosthesis and preparation method thereof
The PCL-PU three-layer composite fiber artificial heart valve is prepared through electrospinning technology, which solves the problems of biocompatibility and service life in traditional heart valve treatment methods, achieves high-performance heart valve preparation, and is suitable for industrial production.
Patent Information
- Application Number
- CN202411491636.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional heart valve treatment methods have poor hemocompatibility of mechanical valves, short service life of biologically derived valves, and immune rejection of allografts, and lack the preparation method with fast, fine, and adjustable structural parameters.
Use static spinning technology to prepare PCL-PU three-layer composite fiber artificial heart valve, including the first layer of disorderly fiber layer, the second layer of orderly fiber layer, and the third layer of disorderly fiber layer. The quality ratio and spinning parameters are optimized to achieve the complexity and performance of the structure.
It achieves excellent mechanical tensile properties, good pore size conditions and excellent biocompatibility of the artificial heart valve, and the preparation method is simple and suitable for large-scale industrial production.
Smart Images

Figure CN119345478A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial heart valve preparation, and in particular to a PCL-PU three-layer composite fiber artificial heart valve and a preparation method thereof. Background Art
[0003] In traditional treatment methods, mechanical valves, biogenic heart valves, and even allogeneic valves are often used to replace diseased heart valves. These methods have their own advantages and disadvantages: mechanical valves are easy to prepare and cheap, but have poor blood compatibility and require lifelong anticoagulants. Biogenic heart valves have good biocompatibility and excellent mechanical properties, but the disadvantage is that they have a low service life. Allogeneic transplants such as porcine heart valves or bovine pericardium can only last for 10-15 years. Allogeneic transplants need to consider immune rejection issues and are unstable sources. The limitations of traditional heart valves require us to actively develop new treatments. Tissue-engineered heart valves are a very promising heart valve in recent years. It can mimic the characteristics of normal tissues and has the ability to grow, repair, and reshape in vivo. Of course, the preparation of tissue-engineered heart valves is not limited to a few methods. Technologies such as weaving and 3D printing can be applied in this direction. But compared with these methods, we need a fast, fine, and adjustable structural parameter structure preparation method. Summary of the invention
[0004] Based on the above content, the present invention provides a PCL-PU three-layer composite fiber artificial heart valve and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a PCL-PU three-layer composite fiber artificial heart valve, which is a three-layer structure, including a first disordered fiber layer, a second ordered fiber layer and a third disordered fiber layer arranged in sequence;
[0007] The first random fiber layer and the third random fiber layer are both polycaprolactone fiber layers;
[0008] The second ordered fiber layer is a composite fiber layer of polycaprolactone and polyurethane;
[0009] The mass ratio of the first disordered fiber layer, the second ordered fiber layer and the third disordered fiber layer is (0.75-1.7):1:(0.75-1.7);
[0010] The mass ratio of polycaprolactone to polyurethane in the second ordered fiber layer is 1:(0.5-2).
[0011] The second technical solution of the present invention is a method for preparing the above-mentioned PCL-PU three-layer composite fiber artificial heart valve, comprising the following steps:
[0012] The polycaprolactone solution is spun onto the mold surface to form a first disordered fiber layer by electrospinning;
[0013] Spinning a polycaprolactone-polyurethane composite solution on the surface of the first disordered fiber layer to form a second ordered fiber layer by electrospinning;
[0014] The third disordered fiber layer is spun from a polycaprolactone solution on the surface of the second ordered fiber layer by electrostatic spinning.
[0015] The present invention discloses the following technical effects:
[0016] The PCL-PU three-layer composite fiber artificial heart valve of the present invention has excellent mechanical tensile properties, good pore size conditions and excellent biocompatibility.
[0017] The preparation method of the invention is simple and easy to be prepared on a large scale in an industrial manner. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 This is an experimental flow chart of the PCL-PU three-layer composite fiber artificial heart valve of the present invention.
[0020] Figure 2 The three-view diagram and 3D schematic diagram of the artificial heart valve mold of the present invention are shown.
[0021] Figure 3 Comsol simulation of the electric field distribution on the surface of the artificial heart valve mold of the present invention.
[0022] Figure 4 The macroscopic morphology and dimensions of the PCL-PU three-layer composite fiber artificial heart valve (PCL / PU=1:1) of the present invention.
[0023] Figure 5It is the SEM image and diameter distribution bar graph of the PCL-PU three-layer composite fiber artificial heart valve (PCL / PU=1:1) of the present invention; wherein, a and b are SEM images of the first and third layers of disordered PCL fibers, respectively; c and d are SEM images of the contact surface between the second ordered fiber layer and the first layer, and the contact surface between the second ordered fiber layer and the third layer, respectively; e is a diameter distribution bar graph of the first layer of disordered PCL fibers; f is a diameter distribution bar graph of fibers in the second ordered fiber layer.
[0024] Figure 6 These are the Raman scattering images and Raman scattering fitting curves of the samples of the present invention; wherein, a is the Raman scattering image of the samples whose second ordered fiber layer components are PU, PCL and PCL / PU (1:1); b is the Raman scattering fitting curve of the samples whose second ordered fiber layer components are PCL / PU (1:1).
[0025] Figure 7 This is a line graph showing the contact angle of the second ordered fiber layer at the initial time point as the components change.
[0026] Figure 8 The figure shows the mechanical properties of the PCL-PU three-layer composite fiber artificial heart valve of the present invention, wherein a is the tensile test curve; b is the Young's modulus bar graph.
[0027] Fig. 9 The cell survival performance of the PCL-PU three-layer composite fiber artificial heart valve extract of the present invention at different time points, wherein a is a bar graph of cell survival rate; b is a line graph of the cell survival rate of each group changing with time.
[0028] Fig.10 These are microscopic photos of live and dead cell staining of cells cultured to the third day; af are live cell staining of the control group and PCL / PU=1:0, 2:1, 1:1, 1:2, and 0:1 groups, respectively; AF are dead cell staining of the control group and PCL / PU=1:0, 2:1, 1:1, 1:2, and 0:1 groups, respectively. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] The "%" described in the present invention, unless otherwise specified, refers to mass percentage.
[0035] It is very important to study and develop new treatment strategies for heart valve disease. Electrospinning, a special fiber manufacturing process, in which a polymer solution or melt is spun by jet in a strong electric field. Under the action of the electric field, the droplet at the tip of the needle changes from a sphere to a cone ("Taylor cone") and extends outward from the tip of the cone to form a filament. In this way, polymer filaments with nanometer diameters can be produced. The morphology and diameter of electrospun fibers are determined by the parameters in the electrospinning process, including solution parameters, process parameters, and environmental parameters. It has been widely used in biomedicine, tissue engineering and other fields. Since the diameter of nanofibers is smaller than the diameter of cells, the structure and biological function of natural extracellular matrix can be simulated. Most tissues and organs in the human body are similar to nanofibers in morphology and structure, which makes it possible for nanofibers to be used in tissue and organ repair; this method can also realize the functions of biomimetic design and drug delivery; and electrospun nanofibers have excellent characteristics such as large specific surface area and high porosity. Nowadays, electrospun fibers made of biocompatible materials can be used to make skin, blood vessels, bones, cartilage, etc.
[0036] Polymers have good spinnability and biocompatibility, and the raw materials are cheap and easy to prepare. They are the mainstream selection interval for electrospun heart valve materials. PCL (poly (caprolactone)), also known as polycaprolactone, is a biodegradable thermoplastic polyester. It has many advantages, making it widely used in various fields. These advantages have rapidly enabled the polymer to be widely used in tissue engineering. PCL materials can be gradually degraded into harmless substances in the body, have good biocompatibility, and are suitable for medical and biomedical fields, such as absorbable sutures, tissue engineering scaffolds, etc.; PCL has good tensile strength and elastic modulus, which enables it to have certain flexibility while maintaining certain mechanical properties; PCL materials have low toxicity and less harm to the environment and organisms, making it a safer material; PCL can be used as a drug carrier to achieve controlled release of drugs and improve the efficacy and therapeutic effect of drugs; PCL has good chemical stability and thermal stability and can be stored for a long time under certain conditions. PCL material has great potential as a material for electrospun heart valves and is one of the indispensable materials for electrospun heart valves.
[0037] PU (Polyurethane) material, full name polyurethane material, is a widely used polymer material with many excellent properties. PU material has excellent mechanical strength, can withstand high pressure and heavy load, and has good wear resistance and corrosion resistance, making it very suitable for manufacturing durable products; PU material is elastic and flexible, and can deform and return to its original shape when subjected to external force, which makes it excellent in cushioning, shock absorption and sealing. PU material has excellent durability and tensile properties, which meets the requirements of artificial heart valves for the buffer layer. It is selected to be compounded with PCL in a certain proportion to prepare artificial heart valves.
[0038] The experimental process of the PCL-PU three-layer composite fiber artificial heart valve of the present invention is as follows Figure 1 As shown, a) a heart valve model is established using SOLIDWORKS modeling; b) an artificial heart valve mold is prepared using 3D printing technology (three views and 3D schematic diagrams are shown in FIG. Figure 2 c) Using Comsol software to simulate the electric field distribution on the surface of the heart valve mold and pre-treat the mold surface; d) Using electrospinning to deposit a polymer composite fiber membrane on the mold surface; e) Peeling off an artificial heart valve sample from the mold; f) Cultivating human valve interstitial cells on the sample surface; g) Using a confocal fluorescence microscope to observe cell adhesion and perform other performance tests.
[0039] The first aspect of the present invention provides a PCL-PU three-layer composite fiber artificial heart valve, which is a three-layer structure, including a first disordered fiber layer, a second ordered fiber layer and a third disordered fiber layer arranged in sequence;
[0040] The first random fiber layer and the third random fiber layer are both polycaprolactone fiber layers;
[0041] The second ordered fiber layer is a composite fiber layer of polycaprolactone and polyurethane;
[0042] The mass ratio of the first disordered fiber layer, the second ordered fiber layer and the third disordered fiber layer is (0.75-1.7):1:(0.75-1.7);
[0043] The mass ratio of polycaprolactone to polyurethane in the second ordered fiber layer is 1:(0.5-2).
[0044] The second aspect of the present invention provides a method for preparing the above-mentioned PCL-PU three-layer composite fiber artificial heart valve, comprising the following steps:
[0045] The polycaprolactone solution is spun onto the mold surface to form a first disordered fiber layer by electrospinning;
[0046] Spinning a polycaprolactone-polyurethane composite solution on the surface of the first disordered fiber layer to form a second ordered fiber layer by electrospinning;
[0047] The third disordered fiber layer is spun from a polycaprolactone solution on the surface of the second ordered fiber layer by electrostatic spinning.
[0048] In a preferred embodiment of the present invention, the concentrations of the polycaprolactone solution and the polycaprolactone-polyurethane composite solution are independently 18-25 wt %.
[0049] In a preferred embodiment of the present invention, the solvent of the polycaprolactone solution is N,N-dimethylformamide.
[0050] In a preferred embodiment of the present invention, the solvent of the polycaprolactone-polyurethane composite solution is a mixture of N,N-dimethylformamide:acetone in a mass ratio of 1:(0.5-2). Further, the mass ratio of N,N-dimethylformamide:acetone in the polycaprolactone-polyurethane composite solution is the same as the mass ratio of polycaprolactone:polyurethane.
[0051] In a preferred embodiment of the present invention, the electrospinning parameters for preparing the first and third disordered fiber layers are set as follows: voltage 15-20 kV, motor speed 400-600 rpm, axial reciprocating speed of the needle holder 1 cm / s, and the distance between the needle and the mold 15-20 cm.
[0052] In a preferred embodiment of the present invention, the electrospinning parameters for preparing the second ordered fiber layer are set as follows: voltage 15-20 kV, motor speed 1400-1800 rpm, axial reciprocating speed of the needle holder 1 cm / s, and the distance between the needle and the mold 15-20 cm.
[0053] The reasons why the electrospinning parameters are set to the above ranges are as follows:
[0054] If the mass ratio between the first disordered fiber layer, the second ordered fiber layer, and the third disordered fiber layer is outside the documented parameter range, the prepared sample will not achieve the expected performance;
[0055] If the concentration of the polycaprolactone solution and the polycaprolactone-polyurethane composite solution is too low, uneven fiber thickness and a large number of beaded fibers will be produced; if the concentration is too high, the solution viscosity will be too high and the nozzle will be blocked.
[0056] During the spinning process, if the voltage is too low, the jet is difficult to form or is easily interrupted; if the voltage is too high, the jet will be unstable and the fibers produced will be uneven in thickness. If the motor speed is too high or too low, the order of the fibers will be affected. If the distance between the needle and the mold is too close, the electric field will be too concentrated and the jet will be unstable; if the distance is too large, the electric field strength will be insufficient and the jet will be difficult to stretch continuously. This will ultimately affect the performance of the prepared sample.
[0057] In a preferred embodiment of the present invention, the mold is modeled after a natural heart valve and then manufactured by 3D printing.
[0058] In a preferred embodiment of the present invention, before preparing the first random fiber layer on the mold surface, the step of coating methyl silicone oil on the mold surface is also included.
[0059] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0060] Raw materials involved in the embodiments of the present invention:
[0061] PCL (polycaprolactone, molecular weight 80,000) is produced by Acmec. PU (polyurethane) is BASF E1185A10 flame retardant polyurethane from Germany. Medical acetone (AR, analytical grade) is produced by Sinopharm Group. N,N-dimethylformamide (DMF, analytical grade AR, 94.5%-95%).
[0062] Experimental equipment involved in the embodiments of the present invention:
[0063] Sample bottle (5 mL), magnet (2 cm), DC high voltage power supply (Tianjin Dongwen, DW-P403-1ACF7), electronic balance (Mettler, ME204 / 02), 24 / 96-well plate (Shanghai Muchen Biotechnology Co., Ltd.), magnetic stirrer (Changzhou Guohua, HJ-4A), scanning electron microscope (ESEM, Quanta 250FEG, FEI), 10T computerized tensile material testing machine (Dongguan Haida Instrument Co., Ltd., HD-B612-S), syringe pump (Baoding Lange Constant Flow Pump Co., Ltd., LSP01-2A), confocal fluorescence microscope (CFM, lica-tcs, SP8), green cell tracker (5-chloromethylfluorescein diacetate, Invitrogen, USA), multifunctional microplate reader (Hangzhou Youmi Instrument Co., Ltd., Opticsmate U1). The cells used in the biological experiments were human aortic valve interstitial cells (immortalized, Xiamen Yimo Biotechnology Co., Ltd.), and the culture medium was 90% DF12+10% FBS+P / S.
[0064] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0065] Example 1
[0066] First, use SOLIDWORKS software to create a simple artificial heart valve model file. The valve is 2.45cm high, 2.306cm in outer diameter, and 1.76cm in inner diameter. The size is modeled after the natural heart valve. The mold for electrospun artificial heart valve is printed according to the model using 3D printing technology (referred to as mold, its 3D schematic diagram and three-view drawing are as follows: Figure 2 shown).
[0067] Template method is a method for preparing artificial heart valves by electrospinning technology. Due to the uneven distribution of charge in the conductor, there is a problem of uneven deposition of electrospun fibers on the mold. In order to make the problem more intuitive, Comsol software was used to simulate the electric field distribution on the mold surface. Figure 3 As shown, it can be seen that the curvature of the conductor surface is different and the electric field strength is also different. More electrospun fibers are deposited at locations with large curvature, and fewer electrospun fibers are deposited at locations with small curvature. In order to ensure that the electrospun fibers are deposited more evenly and that the mechanical strength of the electrospun fiber membrane meets the requirements, the mold needs to be pretreated before electrospinning. Specifically: Use methyl silicone oil (viscosity of 350 centistokes, relative density of 0.97 g / mL at 25°C) to coat the outer edge and sharp parts of the mold, and use a cotton swab to dip about 0.1 mL of methyl silicone oil and apply it to the outer edge and sharp parts of the mold to obtain a pretreated mold. Methyl silicone oil has good chemical stability, lubricity and insulation, which makes it not react with the valve material, facilitating later demolding, and as an insulator, it can form bound charges in the electric field, generate additional electric fields, offset part of the external electric field, and make the electric field lines on the surface sparse, thereby achieving uniform fiber deposition.
[0068] 2 g of PCL was dissolved in 8 g of DMF and stirred on a magnet for 3 hours to prepare a PCL solution with a mass fraction of 20 wt%; 2 g of PU was dissolved in 8 g of medical acetone and stirred on a magnet for 3 hours to prepare a PU solution with a mass fraction of 20 wt%; 2 g of a mixture of PCL and PU (the mass ratios of PCL to PU were 1:2, 1:1, and 2:1, respectively) was dissolved in a mixed solvent of DMF and acetone (when PCL:PU=1:2, DMF:acetone=1:2; when PCL:PU=1:1, DMF:acetone=1:1; when PCL:PU=2:1, DMF:acetone=2:1) and stirred on a magnet for 3 hours to prepare a PCL / PU mixed solution with a mass fraction of 20 wt% (the mass ratios of PCL to PU in the mixed solution (PCL / PU) were 1:2, 1:1, and 2:1, respectively).
[0069] 3 mL of 20 wt% PCL solution was loaded into a 5 mL syringe (the front end of the syringe was connected to a 19G stainless steel needle with an inner diameter of 0.67 mm by a plastic tube). The pretreated mold was fixed on the clamp of the rotating motor, and a needle holder that could move axially was prepared so that its moving axis was parallel to the mold axis. The needle was fixed in a direction parallel to the mold axis. The syringe needle was connected to the positive pole of a high-voltage DC power supply, and the side of the motor that clamped the mold was connected to the negative pole of the power supply. The electrospinning voltage was 15 kV, the motor speed was 400 rpm, the axial reciprocating speed of the needle holder was 1 cm / s, the distance between the stainless steel needle and the electrospinning mold was 15 cm, and a single-layer disordered fiber membrane of PCL was obtained by electrospinning, that is, the first layer of disordered fiber layer was obtained. The motor speed was adjusted to 1800rpm, and the other experimental parameters were the same as before. Then, 4mL of PCL, PU, and PCL / PU mixed solutions (the mass ratios of PCL to PU were 1:2, 1:1, and 2:1, respectively) were used to spin out the second layer of ordered fiber layers in five samples. Then, the operation of the first layer of disordered fiber layers was repeated to spin out the third layer of disordered fiber layers. A small incision was made with a sterile knife to remove the valve from the mold to obtain a PCL-PU three-layer composite fiber artificial heart valve (abbreviated as: sample). The three-layer structure imitates the three-layer structure of a natural human heart valve, and the ordered and disordered arrangement in the sample is to make the mechanical properties of the sample similar to those of a natural valve.
[0070] The samples with the above five component proportions were characterized, the morphology of the samples was characterized by a scanning electron microscope, the hydrophilicity of the samples was characterized by a contact angle tester, the mechanical properties were tested by an electronic universal tensile testing machine, and the component composition of the samples was analyzed by a Raman spectrometer.
[0071] After characterizing the samples, we continued with the biological experiment. Human valvular interstitial cells are an important cell type in heart valves. They participate in the formation of the valve's tissue structure and maintain the stability of the valve's morphology. They have the potential for directional differentiation and can participate in the repair process through proliferation and differentiation when the valve is damaged. This experiment used human valvular interstitial cells for cell growth experiments.
[0072] The characterization and biological experimental results are as follows:
[0073] 1. The diameter of the PCL-PU three-layer composite fiber artificial heart valve prepared in Example 1 is 2.34 cm ± 0.52 mm in outer diameter, 1.78 cm ± 0.32 mm in inner diameter, 2.61 ± 0.21 mm in height, and 0.97 ± 0.24 mm in leaflet thickness. Figure 4 .
[0074] Taking the sample prepared with PCL / PU ratio of 1:1 in Example 1 as an example, the scanning electron microscope (SEM) shows that because the electrospinning inner layer adopts high-speed spinning, the fiber arrangement orientation of the polymer inner layer is obviously stronger than that of the outer layer; in addition, it can be seen that the inner layer of the sample has some bead defects ( Figure 5 This may be because the different solvent tensions at the interface of the two layers affect the evaporation effect. The NanoMeasurer software was used to statistically analyze the distribution of the fiber diameters of the samples. The results are shown in Figure 2. Figure 5 As shown in e and f. For the analysis of the first layer of PCL fibers, the maximum fiber diameter is 0.84μm, the minimum is 0.17μm, and the average diameter is 0.47μm. For the analysis of the middle PCL / PU ordered layer, the maximum fiber diameter is 0.76μm, the minimum is 0.18μm, and the average diameter is 0.46μm. It can be seen from the bar graph that the fibers are concentrated around 0.5μm, and the proportion gradually decreases on both sides.
[0075] 2. Raman scattering and composition analysis
[0076] Generally speaking, Raman spectroscopy is a unique chemical fingerprint of a specific molecule or material, which can be used to quickly confirm the type of material or distinguish different materials. The Raman spectroscopy database contains thousands of spectra. By quickly searching and finding the spectral data that matches the substance being analyzed, the substance being analyzed can be identified. The present invention sorts out the characteristic peaks of ordinary carboxyl polyurethane and poly-ε-caprolactone, see Table 1.
[0077] Table 1. Several main Raman characteristic peaks of PU and PCL
[0078]
[0079] As can be seen from Table 1, the main characteristic peaks distinguishing the two are the vibrations of the triazole ring and benzene ring of PU, and the peak positions correspond to 1524cm-1 、1610cm -1 ; PCL C-COO stretching vibration, peak position is 891cm -1 、958cm -1 .See Figure 6 , which is the Raman scattering image of the second ordered fiber layer of the sample prepared in Example 1, with components of PU, PCL and PCL / PU (1:1). The data of the PCL / PU (1:1) group is extracted, and the PCL / PU (1:1) Raman scattering fitting curve is drawn. It can be seen that the peak position of the fitting peak is 871cm -1 、1091cm -1 、1311cm -1 、1449cm -1 、1621cm -1 、1736cm -1 , we can find the corresponding benzene ring 1610cm -1 The vibrations near the C-COO can be found at 891 cm -1 The nearby stretching vibration indirectly proves that the sample contains two functional groups, benzene ring and C-COO.
[0080] 3. Hydrophilicity and contact angle
[0081] In order to determine the hydrophilicity of a material, experimental tests are required. The present invention uses the contact angle measurement method for testing: a fiber membrane is prepared separately for each layer of the three-layer structure sample to explore the hydrophilicity of each layer. Drop water drops on the surface of the fiber membrane of different layers of the sample, and use a measuring device to capture images of the contact between the droplet and the fiber membrane surface. The angle between the solid-liquid interface is the surface contact angle. The smaller the contact angle, the stronger the hydrophilicity; the larger the contact angle, the stronger the hydrophobicity. Figure 7 As shown, g is a line graph of the contact angle of the second ordered fiber layer at the initial time point as the components change. It can be seen that for the second ordered fiber layer in the middle (PCL / PU composite layer), as the proportion of PU increases, the contact angle becomes smaller and smaller, the hydrophilicity becomes stronger and stronger, and the PCL / PU composite layer transforms from a hydrophobic material to a hydrophilic material. Considering only the hydrophilicity, the higher the hydrophilicity, the more conducive to cell adhesion and spreading. Although the outer layer PCL is a hydrophobic material and has a certain effect on cell adsorption, its excellent degradability, high porosity, biocompatibility, mechanical properties and other advantages make its shortcomings acceptable, making it have great potential in the cardiovascular field. In the future, its cell affinity and anticoagulant balance can also be improved through surface modification and other means.
[0082] 4. Mechanical properties and Young's modulus
[0083] The PCL-PU three-layer composite fiber artificial heart valve is a three-layer polymer structure, similar to the structure of a natural heart valve. Since the internal structure of the natural valve changes with strain, it involves the straightening of highly curled collagen fibers and the rotation of the fibers toward the tensile axis, so the mechanical properties of the leaflets are relatively complex, and billions of times of opening and closing have a great relationship with the durability and tensile resistance of the material. Among the various components of the sample, it is necessary to select the component with the best tensile performance for the subsequent biological experiments. The experiment used a microcomputer-controlled electro-hydraulic servo universal testing machine to measure and generate data along the axial direction. The experimental results are as follows Figure 8 As shown in a. Figure 8 It can be seen from a that when the sample composition is PCL / PU=1:2, the axial mechanical properties of the valve leaflet are the best. Through data processing, combined with the calculation formula of Young's modulus: E=σ / ε, where E is Young's modulus, unit is MPa, σ is stress, unit is kPa, ε is strain, unit is %. The obtained Young's modulus is shown in Figure 8 Middle b.
[0084] When the sample composition is PCL / PU=1:2, the axial Young's modulus of the valve leaflet is the highest, which is 14.70MPa. For natural heart valve leaflets, the axial force is much greater than the radial force. Depending on the individual, genetic, gender, race, blood, blood pressure, etc., the axial elastic modulus of the natural aortic valve leaflet is about 5 to 15MPa. Figure 8 As shown in b, the Young's modulus of the electrospun heart valves of each component is basically within the normal range.
[0085] 5. Cell experiments
[0086] The 96-well plates incubated with CCK-8 reagent for 1, 3, 5, 7, and 14 days were placed in the microplate reader to obtain five sets of absorbance (OD) data at different days. Each set of data at the same time point was analyzed by PCL-PU three-layer composite fiber artificial heart valve samples with different PCL / PU ratios (0.2 cm was added to each well). 2 The samples) and a blank control group without samples were divided into six groups. The expected value of each group of data was calculated according to RGR = A / A 0 ×100% formula (A is the absorbance of samples in different PCL / PU groups; A 0 The cell survival rate was calculated by averaging the absorbance of the blank control group. Fig. 9 As shown:
[0087] Fig. 9The data show the dynamic proliferation process of the experimental group cells over time under the experimental conditions. It can be seen that at any time point when PCL / PU=1:1, the survival rate is the highest and the cell compatibility of the material is the best. As time goes by, the influence of different components on cell survival rate gradually decreases, and finally they are basically the same. The present invention believes that PCL is a polymer material with good biocompatibility, and the cell survival rate should be positively correlated with its proportion. However, since DMF is used to prepare the PCL solution, the solvent has weak cytotoxicity. When the proportion of PCL is too high, the residual DMF solvent will also be more, and the toxic effect of the solvent will be revealed. Therefore, when PCL / PU=1:1, the system is in a dynamic equilibrium with a high survival rate. In the early stage of culture, the number of cells is small, and these effects on cell proliferation cannot be ignored. As time goes by, the cell population will show the adaptability of the cell (adaptability to weak environmental changes), and as the number of cells increases, the proliferation space, metabolic cycle, contact inhibition, etc. will become the main factors limiting the growth of the number of cells. Finally, the cell survival rates of different experimental groups will tend to a stable state with a small difference. The cell survival rate at 14 days was greater than 90%, which indicates that the experimental materials have almost no cytotoxicity and good cell compatibility.
[0088] Fig. 9 The data of the PCL / PU=1:1 experimental group showed that the initial density was 5×10 4 Cells / cm 2 Around the 5th day of culture, the cell line in the 24-well plate reached saturation density, the cells produced density-dependent inhibition, and the cell survival rate no longer increased significantly. The cell lines of other groups reached saturation density on the 7th day, proving that when PCL / PU=1:1, the cell proliferation rate was faster.
[0089] The cells were cultured using culture medium extracts of different components. On the third day of the experiment, the cell growth and adhesion were observed using a fluorescence microscope, and the cells were stained for live and dead. Fig.10 As shown, on the third day, the cell density of each experimental group was appropriate and the adhesion was good. It can be seen that on the third day of the experiment, the distribution of cell density as the experimental sample components changed basically coincided with the experimental results of CCK-8. Compared with the control group, the cell density reached the maximum when PCL / PU=1:1, proving that the cell compatibility was best when the material ratio was PCL / PU=1:1. By comparing the dead cell staining images, it can be found that the cell death rate cultured in the leaching solution of different component materials did not change significantly, and the density was very low, proving that the toxicity of the material did not significantly affect the cell culture.
[0090] From the above conclusions, it can be seen that the PCL-PU three-layer composite fiber artificial heart valve prepared by the present invention has excellent mechanical tensile properties, good pore size conditions, and excellent biocompatibility. When PCL / PU is 1:2, the mechanical properties of the sample are the best. In the cell growth experiment, when PCL / PU is 1:1, the cell survival rate is the highest, and there is basically no cytotoxicity and good biocompatibility. It proves that the method of the present invention is a feasible scheme for preparing artificial heart valves.
[0091] Abnormal heart valve function is the main cause of heart disease and is usually associated with high morbidity and mortality of heart disease. There are many treatments for heart valve disease, but they can be roughly divided into two categories: valve replacement and valve repair. In valve replacement, tissue-engineered heart valves are a research hotspot and key development direction, and the manufacturing strategies of tissue-engineered heart valves are diverse and constantly evolving. The present invention prepares a polycaprolactone-polyurethane (PCL-PU) three-layer composite fiber artificial heart valve based on electrospinning technology. Both PCL and PU have good biocompatibility. After the two materials of PCL and PU are combined, the mechanical strength of the artificial heart valve is higher than that of any single material (PCL or PU). This layered structure makes the artificial tissue-engineered heart valve closer to the natural structure of the mammalian heart, which is conducive to cell proliferation and differentiation.
[0092] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A PCL-PU three-layer composite fiber artificial heart valve, characterized in that: It is a three-layer structure, comprising a first disordered fiber layer, a second ordered fiber layer and a third disordered fiber layer arranged in sequence; The first random fiber layer and the third random fiber layer are both polycaprolactone fiber layers; The second ordered fiber layer is a composite fiber layer of polycaprolactone and polyurethane; The mass ratio of the first disordered fiber layer, the second ordered fiber layer and the third disordered fiber layer is (0.75-1.7):1:(0.75-1.7); The mass ratio of polycaprolactone to polyurethane in the second ordered fiber layer is 1:(0.5-2).
2. A method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 1, characterized in that: The following steps are involved: The polycaprolactone solution is spun onto the mold surface to form a first disordered fiber layer by electrospinning; Spinning a polycaprolactone-polyurethane composite solution on the surface of the first disordered fiber layer to form a second ordered fiber layer by electrospinning; The third disordered fiber layer is spun from a polycaprolactone solution on the surface of the second ordered fiber layer by electrostatic spinning.
3. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: The concentrations of the polycaprolactone solution and the polycaprolactone-polyurethane composite solution are independently 18-25 wt %.
4. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: The solvent of the polycaprolactone solution is N,N-dimethylformamide.
5. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: The solvent of the polycaprolactone-polyurethane composite solution is a mixture of N,N-dimethylformamide:acetone in a mass ratio of 1:(0.5-2).
6. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: When preparing the first and third disordered fiber layers, the electrospinning parameters were set as follows: voltage 15-20 kV, motor speed 400-600 rpm, axial reciprocating speed of the needle holder 1 cm / s, and distance between the needle and the mold 15-20 cm.
7. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: When preparing the second ordered fiber layer, the electrospinning parameters were set as follows: voltage 15-20 kV, motor speed 1400-1800 rpm, axial reciprocating speed of the needle holder 1 cm / s, and distance between the needle and the mold 15-20 cm.
8. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: The mold is modeled after a natural heart valve and then made by 3D printing.
9. The method for preparing the PCL-PU three-layer composite fiber artificial heart valve according to claim 2, characterized in that: Before preparing the first random fiber layer on the mold surface, the method further includes coating methyl silicone oil on the mold surface.